Job Opportunities for Students in their Major after Graduation - A Case Study at Da Lat University - Thi Thuy Dung, Vu; Minh Chien, Le (VNU Journal of Science: Policy and Management Studies, 2023)
Job opportunities after graduation for students and job opportunities in the right major have become important indicators in assessing the training quality of universities in Vietnam today. Based on an online investigation of 264 students who have graduated within the past 10 years at Da Lat University, this article evaluates the job opportunities and jobs in the right major after graduation for university students in the past 10 years, correlated with personal factors, family factors, school factors and the labor market. Research results show that the main job market for post-graduate students is mainly in the public sector, education and training sector, and commune and ward level specialists. While students who work in their majors tend to choose jobs because of their passion and interests, students who have jobs in the wrong majors choose jobs because of economic income. This suggests policy implications for students themselves, universities and the labor market in the present and the future. Keywords : Job opportunities, jobs in the right major, jobs after graduation, students.